Impact on the days of work absenteeism using laboratory tests for discarded Covid-19 in a construction company in Lima. Case Report - Gomero-Cuadra, Raúl (2022)
The World Health Organization (WHO) recommended laboratory tests in symptomatic individuals who meet Covid-19 case criteria as soon as possible from the onset of the disease. To evaluate the benefit of the use of laboratory tests for Covid-19 on work absenteeism, we report the case of a construction company in the city of Lima (Peru), between June 2020 and 2021. It was concluded that the use of laboratory test for suspected cases of Covid-19 had a 54% decrease in days projected absence from work and saving of 51% in the projected cost of days of absence from work in discarded cases of Covid-19. Then, the use of laboratory test for Covid-19 was useful to prevent unnecessary absenteeism.